Study of Serum Hepcidin as a Potential Mediator of the Disrupted Iron Metabolism in Obese Adolescents - Nazif, Hayam K. (Int J Health Sci (Qassim), 2015)
BACKGROUND & AIMS: The prevalence of obesity continues to rise in both developed and developing nations. An association between iron status and obesity has been described in children and adults. We aimed to study the relation between serum hepcidin level and both iron as well as high sensitive CRP status in obese adolescents. MATERIALS & METHODS: This work was conducted on 80 adolescents aging 12–14 years old, divided into two equal groups; obese and non-obese. Anthropometric measurements, determination of haemoglobin, serum iron, total iron binding capacity (TIBC), transferrin saturation, serum ferritin, soluble serum transferrin receptor (sTfR), high sensitive CRP (hs –CRP) and serum hepcidin were performed. RESULTS: Obese adolescents showed significantly lower levels of haemoglobin, serum iron, serum ferritin and transferrin saturation. Significant higher diastolic blood pressure, higher mean TIBC, sTfR, serum hepcidin and hs –CRP were also found. Serum hepcidin level correlated positively with BMI and hs- CRP, but negatively with iron level in obese group. CONCLUSION: These data suggest that hepcidin is an important modulator of anemia in obese patients. Obesity can be considered as a low grade inflammatory state, that stimulates the production of inflammatory markers such as CRP which can up-regulate hepcidin synthesis.